A multi-institutional survey of the quality of life after treatment for uterine cervical cancer: a comparison between radical radiotherapy and surgery in Japan. (7th January 2021) - Kaneyasu, Yuko; Fujiwara, Hisaya; Nishimura, Tetsuo; Sakurai, Hideyuki; Kazumoto, Tomoko; Ikushima, Hitoshi; Uno, Takashi; Tokumaru, Sunao; Harima, Yoko; Gomi, Hiromichi; Toita, Takafumi; Kita, Midori; et al.
Abstract: This study aimed to research the post-treatment quality of life (QOL) between radiotherapy (RT)- and operation (OP)-treated early cervical cancer survivors, using separate questionnaires for physicians and patients. We administered an observational questionnaire to patients aged 20–70 years old with Stages IB1–IIB cervical cancer who had undergone RT or OP and without recurrence as outpatients for ≥6 months after treatment. We divided 100 registered patients equally into two treatment groups ( n  = 50 each). The average age was 53 and 44 years in the RT and OP groups, respectively. The RT group included 34 and 66% Stage I and II patients, respectively, whereas the OP group included 66 and 34% Stage I and II patients, respectively. The OP group included 58% of patients with postoperative RT. Combination chemotherapy was performed in 84 and 48% of patients in the RT and OP groups, respectively. On the physicians' questionnaire, we observed significant differences in bone marrow suppression (RT) and leg edema (OP). On the patients' questionnaire, significantly more patients had dysuria and leg edema in the OP group than in the RT group, and severe (Score 4–5) leg edema was significantly higher in the post-operative RT group than in the OP only group. The frequency of sexual intercourse decreased after treatment in both groups. On the patients' questionnaire, there were no significant differences between the two groups regarding sexual activity. These findings are useful to patients and physicians for shared decision-making in treatment choices. The guidance of everyday life and health information including sexual life after treatment is important.